Expression of CRBN, IKZF1, and IKZF3 does not predict lenalidomide sensitivity and mutations in the cereblon pathway are infrequent in multiple myeloma. Issue 1 (2nd January 2019) - Dimopoulos, Konstantinos; Fibiger Munch-Petersen, Helga; Winther Eskelund, Christian; Dissing Sjö, Lene; Ralfkiaer, Elisabeth; Gimsing, Peter; Grønbaek, Kirsten
Abstract: The immunomodulatory drug thalidomide, and its analogs, lenalidomide, and pomalidomide (IMiDs), have become essential components of the standard treatment for multiple myeloma (MM), and have led to significant improvement of survival in patients with this devastating disease. Cereblon (CRBN), the direct target of IMiDs, has been proposed as a predictive biomarker of response to IMiDs. Using standard immunohistochemistry in formalin-fixed paraffin embedded (FFPE) bone marrow samples of 23 patients treated with a lenalidomide-containing regimen, we found that the malignant plasma cells of all the patients stained positive for CRBN, IKZF1, and IKZF3, regardless of sensitivity to IMiDs. Moreover, we detected no mutations in CRBN, IKZF1, IKZF3, CUL4A, or IRF4, but found expanded TP53 -mutated clones in two out of seven sequential samples. Thus, our data argue against the use of CRBN and its downstream targets as predictive biomarkers of IMiD response in MM and confirm clonal evolution patterns during lenalidomide resistance.